2016
DOI: 10.1021/acs.energyfuels.5b02803
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Chemical Composition of Straight-Run Vacuum Gas Oil and Its Distillates as a Function of the Atmospheric Equivalent Boiling Point

Abstract: The boiling point distribution of petroleum samples remarkably affects the refining process and economic evaluation. The chemical composition of petroleum samples also varies with the boiling range, which is even more important for the processing procedure. In this work, a quick and convenient method was developed to build a clear relationship between boiling points and structures of organic compounds. A straight-run vacuum gas oil (VGO) and its narrow distillates were characterized by Fourier transform ion cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
3
7
0
1
Order By: Relevance
“…These studies reveal that the high compatibility of heavy fractions and upgraded biocrude in SRGO is attributed to their lower oxygen contents (low polarity) being similar to that of the SRGO structure. 36 This observation correlates well with the theoretical predictions of compatibility, made from Hansen double plots. Therefore, fractional distillation plays an important role in dividing biocrude oil into different chemical groups compatible with the fossil fuels to produce drop-in biofuels.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…These studies reveal that the high compatibility of heavy fractions and upgraded biocrude in SRGO is attributed to their lower oxygen contents (low polarity) being similar to that of the SRGO structure. 36 This observation correlates well with the theoretical predictions of compatibility, made from Hansen double plots. Therefore, fractional distillation plays an important role in dividing biocrude oil into different chemical groups compatible with the fossil fuels to produce drop-in biofuels.…”
Section: Resultssupporting
confidence: 85%
“…Similar to the heavy distillate fractions, the low H/C (1.48 wt %) and O/C (0 wt %) ratios in the upgraded biocrude allows the extended aromaticity and lack of oxygen containing functional groups which indicate the complete expulsion of oxygen contents via hydrodeoxygenation. These studies reveal that the high compatibility of heavy fractions and upgraded biocrude in SRGO is attributed to their lower oxygen contents (low polarity) being similar to that of the SRGO structure . This observation correlates well with the theoretical predictions of compatibility, made from Hansen double plots.…”
Section: Resultssupporting
confidence: 85%
“…For [S + Ag] + ions, S1 and S2 class compounds were observed. The identification of individual disulfur species in crude oil was also previously reported. , All the AR samples were rich in S 1 class compounds due to their higher abundance compared to that of the S 2 class compounds. For the sets of high-sulfur AR (AR1 and AR2), the absolute abundance of [HC + Ag] + increased, and [S 1 + Ag] + and [S 2 + Ag] + decreased significantly after HDT.…”
Section: Results and Discussionsupporting
confidence: 62%
“…Moreover, the comparison between atom fractions present in aliphatic groups, namely, hydrogen atoms determined by NMR spectroscopy and carbon atoms estimated using APPI FT-ICR MS, showed a clear correlation between NMR and MS data, despite a number of assumptions required to link double bond equivalent (DBE) values with molecular structures. Wang et al reported the use of detailed chemical compositions in vacuum gas oil and its distillate fractions obtained using FT-ICR MS for establishing the boiling point distribution of the main species . These boiling point distributions were calibrated with gas chromatographic simulated distillations, and after a correction by 50 °C, the FT-ICR MS derived curves matched.…”
Section: Introductionmentioning
confidence: 99%